Application of Molecular Methods and Raman Microscopy Spectroscopy in Agricultural Sciences and Food Technology - Vucelić-Radović, Biljana; Lazić, Dejan; Nikšić , Miomir (Ubiquity Press, 2019)
"This book has been prepared with the aim to present the application of these two state-of-the art technologies in agricultural sciences and food technology, and to explain the protocols for analyses of different plant, animal, microbiological and food samples as well as for different biotechnology procedures. Selected methods and protocols which are used in plant stress physiology, weed science, fruit breeding research, microbial ecology, plant virus and fungus diagnostics, phytobacteriology, fishery, food biochemistry, food materials and food technology are described. Special adaptation of certain protocols is required for application in each of these sciences, for every type of GMO organism, food technology raw material, and food technology product, as well as for every type of bacteria, virus, fungus or fungus-like organism, for each type of raw material in terms of plant host species, plant organs, year period and conditions in the laboratory. Application of molecular methods, primarily qPCR, and Raman microscopy/ spectroscopy in agricultural and food sciences provides substantial opportunity for increased production efficiency, food safety, better product quality and improvement of plant and animal health. This book is aimed for students, scientists and professionals working in the field of agriculture and food technology."